RELIGION AND SOCIAL TOLERANCE: GENERATION Z'S VIEWS ON EXPOSURE TO HOMOSEXUALITY IN THE MASS MEDIA - Quennie Ross Espino; Shairylle Shane Bautista; James Noel Bennagen; Katreena Kaye Tabanao (Religio Education, 2021)
The media exerts a considerable influence on individuals' views, attitudes, and behaviors, particularly on those who lack access to alternative sources of information or are still shaping and forming their identities and perspectives. Attitude towards homosexuality has been different in understanding to type of societies’ cultural and moral development or political circumstance. Arising out of this issue on homosexuality is the idea of natural law and some interpretations of that law as forbidding homosexual sex. Traditionally, homosexuals have been underrepresented and misrepresented in television series and feature films. Homosexual characters have been cast in stereotypically negative roles purely for amusing the audience. In this paper, the researchers were able to analyze how the introduction of content presenting and detailing LGBT individuals and concerns into the mainstream media affects the audiences' attitudes and acceptance of the issue, particularly the Generation Z. The findings indicated that the majority of generation Z residents in Isulan, Sultan Kudarat, aged 15-19, are not influenced by the media in their views on homosexuality, and the interpretation revealed a neutral conclusion in terms of fully tolerating homosexuality in the community.